A total scattering Debye function analysis study of faulted Pt nanocrystals embedded in a porous matrix. Issue 6 (1st November 2016) - Bertolotti, Federica; Moscheni, Daniele; Migliori, Andrea; Zacchini, Stefano; Cervellino, Antonio; Guagliardi, Antonietta; Masciocchi, Norberto
Abstract : An algorithm enabling the active use of deformation fault probabilities in face‐centred cubic metals within the Debye scattering equation approach implemented in the DEBUSSY suite and the subsequent characterization of Pt nanocrystals grown in a nanoporous silica matrix are presented. Abstract : Faulted face‐centred cubic platinum nanocrystals, grown within a nanoporous silica matrix, have been extensively characterized by the Debye function analysis method applied to wide‐angle synchrotron X‐ray total scattering data. A method for building databases of sampled interatomic distances of weakly faulted materials is proposed, maintaining statistical significance and allowing complete populations of differently sized and shaped nanocrystals to be used within the DEBUSSY approach. This study suggests that anisotropic Pt nanoclusters are formed in the presence of a shape‐directing (templating) agent, and tentatively describes the effects of post‐synthetic temperature treatments on fault probability, size, shape and dispersion of the nanocrystal populations. Surface relaxation effects are also observed in the smallest particles.